The development of a personal philosophy and practice of servant leadership : a grounded theory study - Taylor, Simon Michael (Rhodes University, Faculty of Commerce, Department of Management, 2014)
The purpose of this study is to develop a substantive grounded theory explaining the development of a philosophy and the practice of leadership amongst young adults who had attended Hilton College and whom were exposed to their servant leadership development programme. The grounded theory method in this study was developed using conventions identified by Strauss and Corbin (1990) and relying upon a collection of incidents noted during interviews with former students, teachers, housemasters, headmaster and Hiltonian Society board members. In total thirty-six interviews were conducted over a period of four years in South Africa, the United Kingdom and Kenya. Using the grounded theory methodology, an understanding of the theoretical model emerged through the development of a personal philosophy and the practice of servant leadership. Related to the central phenomenon of individual leadership philosophy and practice, the causal condition of opportunity to lead, influenced how the individual philosophy and practice emerged. Strategies used by the participants to nurture their philosophy and practice of leadership were the leadership development programme, community service, feedback and reflection. The data identified the intervening conditions and conditions relating to the context of the leadership philosophy and practice. The consequences of developing a leadership philosophy and practice were related to leadership behaviour; self-esteem; growth; follower relations; empowering of others; and relationship to institutions. The theoretical model illustrated the holistic nature of an individual's leadership philosophy and practice. In this instance, the nature of the data revealed that the individual's leadership philosophy and practice that developed amongst the participants was predominately servant leadership. The different approaches to leadership development were scrutinised with the intention of locating the grounded theory that developed in this study, within the available literature. The literature did provide some useful insights, in particular the social field theory of Bourdieu (1998), which offered a more encompassing explanation and showed much promise in providing an understanding of leadership development. Wheatley's (1999) interpretation of field theory further explained the influence of servant leadership in leadership development. Finally, the researcher developed a set of propositions and recommendations for practice and future research and discussed the value of this research.
Keywords: Hilton College (Pietermaritzburg, -- South Africa); Servant leadership; Grounded theory; Community and school -- South Africa -- KwaZulu-Natal; Student volunteers in social service -- South Africa -- KwaZulu-Natal; Educational leadership -- South Africa -- KwaZulu-Natal